Implementasi Reward dan Punishment dalam Menciptakan Lingkungan Kondusif Belajar Pada Mata Pelajaran Siroh di SDIT Al-Hikmah Depok - Rahmat Ramdhani; Siskha Putri Sayekti; Dul Rohman; M. Badran Fahma (Tarbiatuna: Journal of Islamic Education Studies, 2023)
The purpose of this study was to determine the conducive learning environment for the Siroh subject in grades IV, V and VI at SDIT Al Hikmah Depok through the application of Reward and Punishment. This research is a qualitative research "case study". The research subjects were students in grades IV, V and VI of SDIT Al Hikmah Depok, totaling 78 students. Sources of data come from teachers, data and documents. Data collection techniques are by observation, interviews and documentation. The data validation technique uses triangulation of data sources. Data analysis used descriptive analysis techniques and qualitative analysis techniques. The results of this study indicate that through the application of the Reward and Punishment learning method it can create a conducive learning environment, especially in the Siroh subject. The conclusion of this study is that the application of the Reward and Punishment learning method can create a conducive environment for learning the Siroh subject for grades IV, V and VI SDIT Al Hikmah Depok. The results of the research are: 1) The effectiveness and efficiency of reward and punishment, 2) The teacher can manage the class well through reward and punishment, 3) A conducive environment supports students' comfort. The conclusion of the results of research conducted at SDIT AL-HIKMAH using a case study approach and applying the Reward and Punishment method yielded quite good results. student. Keywords: reward and punishment, conducive learning environment